PENGARUH MODEL KOOPERATIF TIPE ROUND TABLE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SDN 101777 SAENTIS - Luciana Cris May Purba; Edizal Hatmi; Halimatussakdiah; Albert Pauli Sirait; Natalia Silalahi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low learning outcomes of Indonesian language of fifth grade students of SDN 101777 Saentis which are still below the Learning Objectives Achievement Criteria (KKTP). This condition is caused by learning that is still teacher-centered, so that active student involvement in the learning process is still low and has an impact on decreasing motivation and student learning outcomes. This study aims to determine the effect of the Round Table type cooperative learning model on the learning outcomes of Indonesian language of fifth grade students of SDN 101777 Saentis. The research method used is a quasi-experimental design with a pretest-posttest control group design. The population in this study were all fifth grade students totaling 56 students, with samples of class V-A as the experimental class and class V-B as the control class, each consisting of 28 students. The data collection technique used a multiple-choice learning outcome test. Data analysis was carried out through prerequisite tests, namely normality and homogeneity tests, and hypothesis testing using the t-test. The results of the study showed that the average posttest score of the experimental class was 82, while the control class was 72. The results of the hypothesis test showed that the significance value was less than 0.05 (Sig. <0.05), so it can be concluded that there is a significant influence of the use of the Round Table type cooperative learning model on the Indonesian language learning outcomes of class V students of SDN 101777 Saentis.